2017
DOI: 10.1089/cap.2016.0160
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind and Placebo-Controlled Trial of Aripiprazole in Symptomatic Youths at Genetic High Risk for Bipolar Disorder

Abstract: This double-blind trial found that APZ was significantly more efficacious than placebo in reducing symptoms of mania in children and adolescents with cyclotaxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Guanfacine and clonidine can be effective in individuals with co-existing impulse control disorder [90]. Aripiprazole and risperidone are useful for co-existing irritability and aggressive behaviors [183][184][185][186].…”
Section: Other Co-existing Psychiatric Conditionsmentioning
confidence: 99%
“…Guanfacine and clonidine can be effective in individuals with co-existing impulse control disorder [90]. Aripiprazole and risperidone are useful for co-existing irritability and aggressive behaviors [183][184][185][186].…”
Section: Other Co-existing Psychiatric Conditionsmentioning
confidence: 99%
“…Four double-blind, randomized, controlled trials (RCTs) investigated aripiprazole in child and adolescent bipolar disorder and included 458 children and adolescents (Tramontina et al 2009;Findling et al 2012Findling et al , 2013Findling et al , 2017. Most studies found a significant improvement in the manic symptoms, leading to the authorizations listed in Table 1.…”
Section: Efficacy Datamentioning
confidence: 99%
“…Thus, it is possible that we still do not have a good answer for the efficacy of lithium in high‐risk youth based on this single study. A recent randomized controlled trial suggests that in high‐risk youth with subthreshold mania symptoms, aripiprazole may be an effective first‐line treatment option . In this study, high‐risk youth aged 5‐7 who met criteria for either cyclothymia or bipolar disorder‐not otherwise specified showed significant improvement in mood symptoms in the treatment compared to placebo group, but experienced some treatment‐emergent weight gain.…”
Section: Discussionmentioning
confidence: 76%